RISIKO KONSTRUKSI PADA PEMBANGKIT LISTRIK KONVENSIONAL, SEBAGAI MASUKAN UNTUK KONSTRUKSI PLTN PERTAMA DI INDONESIA - dewi, dharu (Badan Pengkajian dan Penerapan Teknologi, 2012)
In general, Construction Risks of the Conventional Power Plants are almost the same with the Construction Risks at the Nuclear Power Plant (NPP). Construction Risks Experience in the Conventional Power Plant can be used as a lesson learned for Construction of the Nuclear Power Plant. This study method covers the survey, the relevant publication and empiric assessment on the real project risk implementation. The input data have been provided from experiences in conventional power plant. Hence, project risks must be control to make sure that construction activities in accordance to agreed shedule and free from cost overruns. This study can be expected will provide a valuable input to project risks of Construction of the NPP. It is concluded that the risk management can be carried out by risk identification, and implement the selected technique or strategyfor reduction of risk, transfer of risk and retention of risk to anticipate the all risks which is take place at the construction. Risk management system must be carried out by well in order to risk can be minimized.